Assessment of the affective and rational bases for urgent decision-making under extreme circumstances - Cosentino, Alejandro César (2017)
In the framework of dual-type theories, decision making is based on two types of information processing: intuitive and reflective. Inspired by that framework, our aims were to develop a brief self-rating measurement instrument to assess the affective and reflective bases for urgent decision-making under extreme circumstances, and to study its psychometric properties. Samples comprising cadets from a military academy, military peacekeeper personnel, and the general population were used. The results showed evidence of acceptable reliability as well as structural, convergent, and known group validity for the Bases for Urgent Decisions under Extreme Circumstances inventory (BUDECI), the new 8-item inventory.